2011
DOI: 10.1159/000324168
|View full text |Cite
|
Sign up to set email alerts
|

Effects of N-Acetylcysteine on Renal Hemodynamics in Contrast Media-Induced Nephropathy

Abstract: Background: N-acetylcysteine (NAC) has been proposed to prevent radiocontrast nephropathy in high-risk patients. Methods: The effect of single-dose and prolonged administration of NAC before application of either the ionic, high-osmolar radiocontrast agent diatrizoate sodium (DTZ) or the nonionic, low-osmolar radiocontrast agent iohexol (IOH) in a rat model combining uninephrectomy, salt depletion, and administration of indomethacin was explored. Arterial blood pressure and total, cortical, and medullary blood… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 110 publications
1
1
0
Order By: Relevance
“…Optical and electron microscopy examination of renal tissue in the contrast group showed severe damage, with vacuolar degeneration of renal tubular epithelial cells, nuclear pyknosis and lysis, mitochondrial swelling in renal tubular epithelial cells and disorder of the marginal ridge structure. The results of our study are basically consistent with those reported by others at home and abroad ( Krzossok et al, 2011 ; Ozkan et al, 2012 ; Gong et al, 2013 ). Compared with the contrast group, the degree of renal injury in the nano liposome and hydration groups was significantly reduced, but the degree of renal injury in the nano liposome group was clearly less, indicating that nano liposome administration works better than hydration.…”
Section: Discussionsupporting
confidence: 93%
“…Optical and electron microscopy examination of renal tissue in the contrast group showed severe damage, with vacuolar degeneration of renal tubular epithelial cells, nuclear pyknosis and lysis, mitochondrial swelling in renal tubular epithelial cells and disorder of the marginal ridge structure. The results of our study are basically consistent with those reported by others at home and abroad ( Krzossok et al, 2011 ; Ozkan et al, 2012 ; Gong et al, 2013 ). Compared with the contrast group, the degree of renal injury in the nano liposome and hydration groups was significantly reduced, but the degree of renal injury in the nano liposome group was clearly less, indicating that nano liposome administration works better than hydration.…”
Section: Discussionsupporting
confidence: 93%
“…The early postprocedural period was thought to be the rush hour of contrast media excretion, causing rapid and prolonged renal hypoperfusion [4,5], which was the critical time window for CIN. Therefore, the decrease in blood pressure in the early phase after PCI may affect the development of CIN.…”
Section: Introductionmentioning
confidence: 99%